Pengaruh Profitabilitas, Struktur Aset dan Risiko Bisnis Terhadap Struktur Modal (Studi Pada Perusahaan Sub Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia) - Sri Moniaga Putri; Dessi Susanti (Universitas Negeri Padang, 2023)
This study purpose is to decide the profitability effect, structure of asset, and risk of business on the structure of capital on firms in the apparel and textiles subsector listed on Exchange of Stock in the Indonesia”. This research is classified as research of causative. The study population are all firms in the apparel and textiles subsector listed on exchange of stock in the Indonesia in 2017-2020. The study sample was determined by purposive sampling so that a sample of 13 companies was obtained. Data secondary data was used obtained from www.idx.co.id.The data analysis technique used is analysis of multiple regression using the SPSS program. The results of this study indicate that profitability, asset structure and business risk together have a positive effect on the structure of capital on firms in the apparel and textiles subsector listed on the exchange of stock in the Indonesia. Profitability has a positive effect on the structure of capital on the firms in the apparel and textiles subsector listed on the exchange of stock in the Indonesia. Asset structure has a negative effect on capital structure of textile and garment sub-sector companies listed on the exchange of stock in the Indonesia, while business risk has no effect on structure of capital on textile and garment sub-sector companies listed on the exchange of stock in the Indonesia.